Judicial procedure in the event of the absence of the of the Federal Public Prosecutor's Office at the pre-trial hearing: (does the principle of real truth still exist?) (Revista do Tribunal Regional Federal da 3ª Região, 2012)
This study analyzes a recent ruling by the Superior Court of Justice, which annulled a case in which the judge, in the absence of the Public Prosecutor's representative, asked questions of the prosecution witness. In addition to criticizing the Superior Court's position, a reflection is made on the principle of real truth.
Keywords: judicial procedure; investigation hearing; absence of the Public Prosecutor's Office representative; principle of the real truth; opposition of witnesses